Effect of Extreme Cooling on Indices of Vegetative Regulation of Cardiac Rhythm in Rats of Different Age Groups - Babijchuk, V. G.; Kozlov, A. V. (Problems of Cryobiology and Cryomedicine, 2008)
Extreme temperature effects (–120°C) due to the activation of own homeostatic regulatory systems were established to significantly increase organism’s adaptation possibilities, independently on age. This fact is confirmed by the data of spectral analysis of cardiac rhythm variability, testifying to an increase in total spectral capacity as a result of activity improvement of both vegetative centers and humoral link of regulation. In aged animals at the background of extreme cryotherapy the process of cardiac rhythm control passes from slow humoral and metabolic regulation level into a rapid vegetative one.